データ同化手法の多面性と応用展開 - 中野, 慎也; Shin'ya, Nakano (2017)
第8回極域科学シンポジウム/特別セッション：[S] 先端的技術で切り開く極域科学 －極域観測における計測、分析、解析の最前線－ 12月7日（木）国立極地研究所 2階大会議室 The Eighth Symposium on Polar Science/Special session: [S] Polar science developed by leading-edge technology - on the frontiers of measurement and analysis in polar science - Thu. 7 Dec./2F Auditorium, National Institute of Polar Research conference object